2009
DOI: 10.1016/j.amjcard.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blood Hematocrit and Erythrocyte Deformability on Adenosine 5′-Diphosphate Platelet Reactivity in Patients With Acute Coronary Syndromes on Dual Antiplatelet Therapy

Abstract: Previous studies have explored the association between hemorheologic alterations and aspirin resistance, pointing out the possible interaction between hematologic components and platelet responsiveness to antiplatelet drugs. The aim of this study was to evaluate the association between hemorheologic variables and residual platelet reactivity in patients with acute coronary syndromes (ACSs) who underwent percutaneous coronary intervention on dual antiplatelet therapy. The study population included 528 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Use of statins remained an independent predictor of aspirin resistance even after adjustment for risk factors and medication use (OR 5.92, 95% CI: 1.83-16.9, P < 0.001). The importance of impaired hemorheological parameters in the development of aspirin resistance was confirmed by another study conducted by our workgroup and it was also confirmed by independent studies [50,51] . One potential explanation is when plasma fibrinogen levels increase red blood cells adhere and release ADP, which is a potential agonist of platelet aggregation.…”
Section: Aspirin Resistancesupporting
confidence: 70%
“…Use of statins remained an independent predictor of aspirin resistance even after adjustment for risk factors and medication use (OR 5.92, 95% CI: 1.83-16.9, P < 0.001). The importance of impaired hemorheological parameters in the development of aspirin resistance was confirmed by another study conducted by our workgroup and it was also confirmed by independent studies [50,51] . One potential explanation is when plasma fibrinogen levels increase red blood cells adhere and release ADP, which is a potential agonist of platelet aggregation.…”
Section: Aspirin Resistancesupporting
confidence: 70%
“…These findings are in accordance with previously published observations [23,24] and suggest that the analysis of standard morphology, i.e. PTL count, may be helpful in the prediction of ASA and CLO responsiveness.…”
Section: Discussionsupporting
confidence: 82%
“…Some hemorheologic variables are also associated with high on-treatment platelet reactivity in patients with ACS on dual antiplatelet therapy. In particular, decreased erythrocyte deformability is significantly associated with increased platelet aggregation induced by ADP 29. A possible explanation for this association is that erythrocytes with decreased deformability tend to release a larger amount of ADP in the circulation compared to those without93 and this released ADP can compete with clopidogrel for purinergic receptors present on the platelet surface.…”
Section: Nonpharmacogenetic Factors Influencing Response To Clopidogrelmentioning
confidence: 99%